2009
DOI: 10.1016/j.ejcts.2009.04.067
|View full text |Cite
|
Sign up to set email alerts
|

Routine placement of an intercostal chest drain during video-assisted thoracoscopic surgical lung biopsy unnecessarily prolongs in-hospital length of stay in selected patients☆☆☆

Abstract: The routine use of an intercostal chest drain after VATS lung biopsy unnecessarily increases the length of hospital stay without reduction in the incidence of pneumothorax.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 5 publications
(4 reference statements)
0
27
0
6
Order By: Relevance
“…6,7 In addition, patients without a chest tube can be postoperatively discharged within 24 h. Thoracoscopic wedge resection of the lung could be considered an outpatient procedure. [2][3][4][5] However, some surgeons believe that keeping the chest tube in place for 1-2 days after lung resection provides a "safety net" and reduces the incidence of early postoperative complications, such as pneumothorax or unexpected hemorrhaging. Therefore, the most important consideration is the proper selection of patients who will not postoperatively require chest tube placement.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…6,7 In addition, patients without a chest tube can be postoperatively discharged within 24 h. Thoracoscopic wedge resection of the lung could be considered an outpatient procedure. [2][3][4][5] However, some surgeons believe that keeping the chest tube in place for 1-2 days after lung resection provides a "safety net" and reduces the incidence of early postoperative complications, such as pneumothorax or unexpected hemorrhaging. Therefore, the most important consideration is the proper selection of patients who will not postoperatively require chest tube placement.…”
Section: Discussionmentioning
confidence: 98%
“…Several methods for the postoperative management without chest tubes and early chest tube removal after VATS have been reported. [1][2][3][4][5][6][7] Earlier chest tube removal after the operation augments the less invasive VATS procedure, and also contributes to a shorter hospital stay and improved cost-effective benefi ts. 6,7 In addition, patients without a chest tube can be postoperatively discharged within 24 h. Thoracoscopic wedge resection of the lung could be considered an outpatient procedure.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Chest drain use remains controversial, as thoracotomy incisions may damage the intercostal nerves and lead to chronic neuropathy (39). Satherley et al (40) reported that the use of an intercostal chest drain following lung biopsy increased the period of hospitalization and Nakashima et al (41) reported that postoperative morbidity did not increase following thoracoscopic lung wedge resection without a chest tube. Luckraz et al (42) demonstrated that there was no requirement for an intercostal chest drain in patients that had received VATS lung resection if no air leakage was noted during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Однако до настоящего времени нет ни одной области хирургии, в которой протокол как ухода за дренажами, так и времени их удаления был бы стандартизован. В большом количестве исследований по-казана не только целесообразность раннего удаления дре-нажа из плевральной или брюшной полости, но и возмож-ность полного отказа от его установки в отдельных ситуа-циях [27,38,42]. Тем не менее в большинстве исследова-ний подчеркнута необходимость полного хирургического контроля гемо-и/или аэростаза при решении вопроса об отказе от дренирования.…”
Section: протокол ускоренной реабилитацииunclassified